Grade-7 Students’ Negotiation during the Engineering Design Processes Regarding the Status of Their Argumentation Training - Tuğ, Sayıner; Namdar, Bahadır (Science Insights Education Frontiers, 2024)
This study aimed to investigate grade-7 students’ negotiation during the engineering design process regarding the students’ status of argumentation training. The participants were 33 students studying at a public urban middle school in Turkey. They worked in small groups on four engineering design tasks about electricity and light. Data were collected through small group audio recordings, student worksheets, and the observation. The data were analyzed by using content analysis. The results indicated that negotiation patterns were similar across all groups. However, differences were found between the group that received argumentation training and the one that did not receive in terms of proposing ideas for material design, using justifications when in agreement with others, counter proposing and acquiring information for better planning and altering the design, and critiquing for design advantages and disadvantages.